Exercise Activity Analysis and Paralympian Recovery Athletics During The Covid-19 - Ramadhani, Dyah Sukma; Ashadi, Kunjung (UNIVERSITAS NEGERI MAKASSAR, 2021)
The covid-19 pandemic period caused activities and the need for recovery paralysis to be disrupted, in other studies not much has analyzed training activities and athletic recovery during the covid-19 pandemic. Motion outside this research use non-experimental quantitative research methods and is written descriptively. The data was obtained by filling out the Google Form filled in by 13 Paralympian respondents. The data were analyzed by calculating the percentage. Thes results are Paralympian with sleep recovery 86% with the category always score and exercise activity reaches a percentage rate of 74,9%, the frequency of exercise gets an average of 51,3% with the occasional category, the intensity of the exercise has an average number of 63,2% with the frequent category, and the duration of exercise has an average rate of 53,8% with occasional category. The conclusions are that when the covid-19 pandemic hit, with the government’s provisions that physical distancing does not limit the paralysis to carry out activities and carry out maximum recovery. The sleep to be the highest percentage of 86% with the always the data average reaches 73 which is the value of 81%-100%, that the exercise activity or anaerobic and aerobic exercise has an average number of 74,9 with the frequent category, the intensity of light-moderate exercise has an average number the average was 63,2 with the frequent category and the exercise duration had 30-45 minutes a day the mean score was 53,8 with the occasional category. Suggestion by staying consistent in doing exercise activities gradually.